Metamaterials: Photo‐driven Super Absorber as an Active Metamaterial with a Tunable Molecular‐Plasmonic Coupling (Advanced Optical Materials 8/2014). Issue 8 (August 2014) - Hedayati, Mehdi Keshavarz; Javaheri, Mojtaba; Zillohu, Ahnaf Usman; El‐Khozondar, Hala Jarallah; Bawa'aneh, Muhammad S.; Lavrinenko, Andrei; Faupel, Franz; Elbahri, Mady
<x xml:space="preserve">Abstract</x> M. Elbahri and co‐workers show on page 705 how photochromic molecules placed on top of a highly reflective metal show very strong optical absorption upon illumination with UV light. A tunable metamaterial perfect absorber is demonstrated, wherein the absorption/reflection can be adjusted by UV or white‐light irradiation. The high confinement of the light by the molecule upon UV irradiation (no reflection, left side) is shown in this image, while the white light illuminated molecules (right side) can not remove the reflection of the base metal (gold). <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>